Dinâmica e estrutura da comunidade procarionte da represa de Itupararanga - bacia do Rio Sorocaba - SP - Soares, Laís Américo (2013)
This work aimed to quantifier the archaeal and bacterial communities by real time PCR, that shown the number of copies of 16S gene, rDNA into the water samples and to compare the archaeal and bacterial profiles on the PCR/DGGE technique as well as relate them with environmental variables in two points, dam and input on the Itupararanga reservoir, Sorocaba s basin. The bacterial density on the sediment (6,09 x108 e 2,56 x 109, dam and input, respectively) was more than water column (6,79 x 107 e 6,55 x 107, dam and input, respectively) this can be attributed to increase of the nutrients concentration from the surface to bottom. The bacterial (6,09 x 108 e 2,56 x 109 dam and input, respectively ) and archaeal (2,31 x 102 e 4,49 x 102 dam and input, respectively) quantities on the reservoir were more in the water column than in the sediment, which can be caused by the higher nutrients concentration in the top and the lees nutrients concentration in the bottom of Itupararanga reservoir. Since the canonical correspondence analysis has been possible, identify that the archaeal community has correlated with profundity and ammonia concentration suggesting ammonia oxidizing archaea s presence and abundance. The bacterial community quantity has correlated with physical chemical properties like pH and dissolved oxygen suggesting the environmental variables influence the group s abundance. Richness has correlated with nutrients distribution like orthophosphate concentration suggesting that the resources may limit the communities.